Livro didática de física: qualidade e utilidade em sala de aula - Silva, José Pereira da (2010)
In this paper we have analyzed aspects concerned with the quality and usefulness of the Physics textbook, in the context of the classroom, which we consider relevant, regarding to the construction of meaningful learning of this curriculum component. For this, we have taken as reference the theoretical assumptions of some researchers in education and have correlated them with information provided by everyday experience, during the long period we have stayed in the classroom, teaching physics in High School. The study we have performed had as a main objective, as previously mentioned, to analyze intrinsic requirements in the textbooks of Physics, particularly regarding their usefulness as teaching tools. For this, as a general point, we have made a quick story about the books adopted by PNLEM since 2008, once we understand that these textbooks are, at the moment, and will probably continue to be the most widely used in the public schools of our country in coming years, hence their relevance in this context. Then, we have delimitated our research, centering on the book: Física Volumes 1, 2 and 3 (Antonio Máximo Ribeiro da Luz e Beatriz Alvarenga Álvares), which is the textbook adopted, at the time, for us (teachers of Physics) of IFPB / campus - Cajazeiras. We understand that, maybe this way, we can motivate those who are, directly or indirectly, involved in the teaching and learning process of Sciences, particularly of Physics, to reflect more deeply about the quality and usefulness of the textbook of this curriculum component in High Schools . Face to this discussion, we also hope that, within this context, conditions may arise envisioning the need to get an overview about the origin, development and purpose of Science, more specifically of Physics, if we want our students, especially the High School ones, to dig into a search for a more comprehensive understanding of the contents which involve this curriculum component.